Optimization of Motorcycle EMP Values Based on Traffic Flow Dynamics in the Jabodetabek Metropolitan Area - Nugroho, Adi (Smart City, 2024)
The research on optimizing Equivalent Motorized Passenger Car Unit (EMP) values for motorcycles in Jabodetabek addresses the pressing traffic challenges in Indonesia's largest metropolitan area. With rapid population growth and increasing motor vehicles, accurate traffic flow modeling is crucial. Motorcycles, dominant in Jabodetabek's transport, are often misrepresented by EMP values equivalent to cars, leading to inaccurate traffic estimates. Adjusting EMP values, especially in macroscopic modeling, is imperative for precise transportation planning. This study explores the necessity of recalibrating EMP values for motorcycles, crucial for sustainable development and future transportation technology integration. By analyzing traffic dynamics and adjusting EMP values, the research aims to provide more accurate depictions of traffic conditions, essential for effective policymaking and infrastructure planning. Results indicate a clear correlation between traffic density and motorcycle efficiency, emphasizing the need for tailored EMP values. This research offers insights for improving transportation planning and addressing future metropolitan traffic challenges.